DIGITAL MARKETING STRATEGY THROUGH TIKTOK SHOP TO INCREASE UMKM SALES VOLUME - Nerisca Yayang Pratiwi; Safriza Ledi Prayesa; Iin Wahyu Setianingsih; Sandy Prasetyo Widodo; Dauzi; Agung Firman Sahril; Muhammad Riansyah (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
The rapid development of digital technology has transformed marketing practices, particularly through the emergence of social commerce platforms such as TikTok Shop, which integrate content creation, interaction, and transaction within a single ecosystem. This study aims to examine the effectiveness of digital marketing strategies implemented through TikTok Shop in increasing the sales volume of Micro, Small, and Medium Enterprises (UMKM). Employing a quantitative research approach with an explanatory design, this study collected data from UMKM actors actively utilizing TikTok Shop as a digital marketing channel. Data were obtained through structured questionnaires and analyzed using descriptive and inferential statistical techniques to assess the relationship between TikTok Shop- based digital marketing strategies and UMKM sales performance. The results indicate that digital marketing strategies through TikTok Shop have a positive and statistically significant effect on UMKM sales volume. Key strategic elements, including content creativity, live streaming utilization, and active consumer interaction, were found to enhance product visibility, strengthen consumer trust, and stimulate purchasing decisions. The discussion highlights that TikTok Shop functions not only as a promotional medium but also as an integrated social commerce system that supports efficient marketing communication and transaction processes. This study concludes that TikTok Shop-based digital marketing represents a strategic and sustainable approach for improving UMKM sales performance and competitiveness in the context of ongoing digital transformation.